Student Services in China - Arnold, Karen; Zhu, Hong (International Higher Education, 2011)
The profession of student affairs in Chinese higher education is expanding and taking on new forms in response to increased postsecondary participation and changing economic and social conditions. Universities throughout China are establishing new and reconfigured administrative positions and structures charged with non-academic student services such as career advising, mental health counseling, and financial aid advising. Government statements, new graduate degree programs, and research on college students point to an emergent student development movement in China whose contours are still forming.